Creative quest - Questlove 1971-; Greenman, Ben 1969- (Ecco, an imprint of HarperCollins Publishers, 2018)
"From the mind of Questlove comes a unique new guide to creativity...exploring his origins as an artist, paying tribute to the people and ideas that have inspired him, and passing along lessons learned"...